Diseño de investigación, levantamiento de información, procesamiento y análisis de estadísticas del turismo receptor nacional e internacional en Loja año 2013. - Betancourt Ludeña, Johana Vanessa (2014)
This project shows the analysis of national and international inbound tourism in the city of Loja in 2013 and aims to know the motivations that tourists have when choosing Loja as their destination. This work consists of three chapters: the first chapter is a situational analysis of the city of Loja for which we collected information of the city about its physical, social, economic and political areas; The second chapter discusses the existing methodology to determinate the tourist profile where we used the quantitative method to survey the airport, bus terminal, hotels and some gas stations located on the outskirts of the city. These surveys were made in August when exists more tourists due to the holiday season and the arrival of the Cisne virgin to the city. Finally in the third chapter we described the tourist profile, one for tourists arriving by air, another for tourists who came by public transportation and another for the people who came in their own vehicle, and then determine the global profile of the tourist that comes to Loja.